A lithium ion adsorption material and its preparation method and application
By using polyvinyl chloride as the core layer and lithium ion sieve as the shell layer in the lithium ion sieve adsorbent, the problem of reducing adsorption capacity during the powdered lithium ion sieve molding process is solved, and the preparation of efficient and durable lithium ion adsorption materials is achieved.
Patent Information
- Application Number
- CN202310183972.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-02-17
AI Technical Summary
Powdered lithium-ion sieve leads to a decrease in specific surface area and a decrease in adsorption capacity during molding, limiting its widespread use in industrial applications.
Polyvinyl chloride (PVC) is used as the core layer, and lithium ion sieve and pore-generating agent are used as shell layers on the outer layer to prepare lithium ion adsorption materials by spinning molding.
The utilization rate of lithium ion sieve is improved, the pressure resistance of molded particles is enhanced, and the high adsorption capacity and acid-base resistance are maintained, reducing production costs.
Smart Images

Figure CN116212830B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium adsorption, and in particular to a lithium ion adsorption material and a preparation method and application thereof. Background Art
[0002] Lithium is one of the important rare metals that is closely related to the national economy and people's lives. Its metal and compounds are widely used in glass, ceramics, chemicals, medicine and other fields.
[0003] Lithium extraction by adsorption is a new type of lithium extraction process from salt lakes developed in recent years. Lithium extraction by adsorption of lithium ion sieve is a relatively mature green lithium extraction method at this stage, and is very suitable for separating and extracting lithium ions from salt lake brine with a high magnesium-lithium ratio. Powdered lithium ion sieve has the advantages of large specific surface area, sufficient solid-liquid contact, high adsorption capacity, and fast adsorption rate. However, due to its difficulty in recycling and large-scale application, powdered lithium ion sieve limits its industrial application. In order to solve the problem of difficult industrial application of powdered lithium ion sieve, it is necessary to shape and granulate the powdered lithium ion sieve.
[0004] The existing molding technologies for lithium ion sieves include bonding molding, spinning molding, polymerization molding, etc. However, molding will cause the specific surface area of the lithium ion sieve to decrease, and the adsorption capacity will be greatly reduced. Chinese patent document CN114345291A discloses a method for preparing a titanium-based lithium ion sieve adsorbent with high adsorption capacity. The molding method adopts slurry granulation and water bath curing molding. Chinese patent document CN111992155A discloses a chitosan-lithium ion sieve composite pellet and its preparation method and application. The lithium ion sieve is molded by polymer cross-linking technology, but the preparation process is relatively complicated and the adsorption capacity is low. In recent years, in order to improve the specific surface area and adsorption capacity of molded adsorbents, adsorbent molding methods have become a research hotspot.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One aspect of the present invention relates to a lithium ion adsorption material, wherein the lithium ion adsorption material comprises a core and a shell;
[0007] The core of the lithium ion adsorption material comprises: polyvinyl chloride; the shell of the lithium ion adsorption material comprises: polyvinyl chloride, a lithium ion sieve and a porogen.
[0008] The lithium ion adsorption material has large adsorption capacity, strong acid and alkali resistance and stable adsorption capacity.
[0009] Another aspect of the present invention also relates to a method for preparing a lithium ion adsorption material, comprising the following steps:
[0010] Spinning, acidifying and washing the spinning solution A and the spinning solution B;
[0011] Wherein, the spinning solution A comprises: polyvinyl chloride; the spinning solution B comprises: polyvinyl chloride, lithium ion sieve and porogen.
[0012] The method for preparing the lithium ion adsorption material has a simple preparation process and is economical and environmentally friendly. The lithium ion adsorbent produced has strong acid and alkali resistance, large adsorption capacity and low production cost.
[0013] Another aspect of the present invention also relates to a method for adsorbing lithium ions, using the lithium ion adsorption material to adsorb lithium ions.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] (1) The lithium ion adsorption material provided by the present invention has a large adsorption capacity and strong acid and alkali resistance. The inner part is polyvinyl chloride, and the main component of the outer layer is lithium ion sieve. In the process of engineering application, due to the control of ion diffusion rate, the internal adsorbent often does not play an effective role. Therefore, the internal pure PVC slurry is used to replace the lithium ion sieve slurry for spinning molding. This can not only improve the utilization rate of the lithium ion sieve and reduce the production cost, but also play a certain supporting role and enhance the pressure resistance of the molded particles.
[0016] (2) The preparation method of the lithium ion adsorbent material provided by the present invention has a simple preparation process and is economical and environmentally friendly. The lithium ion adsorbent produced has strong acid and alkali resistance, large adsorption capacity and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 It is a schematic diagram of the structure of lithium ion adsorption material;
[0019] Figure 2 Schematic diagram of the spinneret structure;
[0020] Figure 3 This is a cross-sectional view of the double-layer filamentous lithium ion sieve of Example 1;
[0021] Figure 4 This is a cross-sectional view of the double-layer filamentous lithium ion sieve of Example 2;
[0022] Figure 5 This is a data chart for the long-term operation evaluation of a double-layer filamentary-molded lithium-ion sieve. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0024] One aspect of the present invention relates to a lithium ion adsorption material, the lithium ion adsorption material comprising a core and a shell;
[0025] The core of the lithium ion adsorption material comprises: polyvinyl chloride; the shell of the lithium ion adsorption material comprises: polyvinyl chloride, a lithium ion sieve and a porogen.
[0026] Lithium ion adsorption material, the structure of the formed lithium ion adsorption material is shown in Figure 1 , large adsorption capacity, strong acid and alkali resistance; the interior is polyvinyl chloride, and the main component of the outer layer is lithium ion sieve. In the process of engineering application, due to the control of ion diffusion rate, the internal adsorbent often does not play an effective role. Therefore, the internal acid and alkali resistant pure PVC slurry is used to replace the lithium ion sieve slurry for spinning molding, which can not only improve the utilization rate of the lithium ion sieve and reduce production costs, but also play a certain supporting role and enhance the pressure resistance of the formed particles.
[0027] Preferably, the thickness ratio of the core to the shell of the lithium ion adsorption material is 1:(3-5) (eg, 1:3, 1:4 or 1:5).
[0028] Preferably, the shell of the lithium ion adsorption material comprises, by mass:
[0029] 140-170 parts (e.g., 140, 150, 160 or 170 parts) of polyvinyl chloride, 30-60 parts (e.g., 30, 35, 40, 45, 50, 55 or 60 parts) of lithium ion sieve, and 25-170 parts (e.g., 25, 35, 45, 55, 65, 75, 80, 90, 100, 110, 120, 130, 140, 150, 160 or 170 parts) of porogen.
[0030] Preferably, the lithium ion sieve comprises: a titanium-based adsorbent and / or an aluminum-based adsorbent.
[0031] Preferably, the porogen includes: polyvinyl pyrrolidone and / or polyethylene glycol.
[0032] Another aspect of the present invention also relates to a method for preparing the lithium ion adsorption material, comprising the following steps:
[0033] Spinning, acidifying and washing the spinning solution A and the spinning solution B;
[0034] Wherein, the spinning solution A comprises: polyvinyl chloride; the spinning solution B comprises: polyvinyl chloride, lithium ion sieve and porogen.
[0035] The preparation method of the lithium ion adsorption material has a simple preparation process and is economical and environmentally friendly. The lithium ion adsorbent produced has strong acid and alkali resistance, large adsorption capacity, stable adsorption capacity and low production cost.
[0036] Preferably, the coagulation bath temperature of the spinning is 60-80°C (eg, 60°C, 65°C, 70°C, 75°C or 80°C).
[0037] Preferably, the air bath length of the spinning is 0.1 to 1 m (eg, 0.1 m, 0.2 m, 0.3 m, 0.4 m, 0.5 m, 0.6 m, 0.7 m, 0.8 m, 0.9 m or 1 m).
[0038] Preferably, the acidification temperature is 55-65°C (eg, 55°C, 57°C, 59°C, 61°C, 63°C or 65°C).
[0039] Preferably, the acidified acid solution has a concentration of 0.01 to 0.1 M (eg, 0.01 M, 0.02 M, 0.05 M, 0.08 M or 0.1 M).
[0040] Preferably, the spinning solution A is prepared by using dimethylformamide (DMAC) as solvent, adding polyvinyl chloride (PVC) so that the mass ratio of DMAC to PVC is 1.5:1 to 0.5:1, the viscosity of the casting solution is 5000-200000 mPa·s, and then stirring in an oil bath at 50-80°C for 5-12 hours.
[0041] Preferably, the spinning solution B is prepared as follows: 200 g of PVC and lithium ion sieve in total, 1.2-1.8 times the total mass of PVC and lithium ion sieve as solvent dimethylformamide (DMAC), porogen polyvinyl pyrrolidone (PVPK15, PVPK30, PVPK60), polyethylene glycol with a degree of polymerization of 400-2000, and the mixed materials are placed in a 60°C oil bath and stirred for 5h-15h.
[0042] Preferably, a spinning liquid tank and a spinneret are installed. The schematic diagram of the spinneret structure is shown in Figure 2The stirred material is double-spun at a coagulation bath temperature of 60-80℃. The spinning solution is pumped by a metering pump. The pumping speed of the A liquid is 5-10Hz / min, and the pumping speed of the B liquid is 15-50Hz / min. The inner and outer liquids are extruded from the spinneret at the same time. The inner layer is polyvinyl chloride, and the outer layer is a liquid with lithium ion sieve as the main component. The air bath length is 0.1-1m. After the coagulation bath, the film is solidified by phase inversion reaction. After the spinning is completed, the silk is heat-treated in pure water at 60-80℃ for 2-6h.
[0043] Preferably, a spinning liquid tank and a spinneret are installed, and the stirred material is subjected to double-layer spinning at a coagulation bath temperature of 60-80°C. The spinning liquid is pumped by a metering pump, and the pumping speed of the A liquid is 5-10Hz / min, and the pumping speed of the B liquid is 15-50Hz / min. The inner and outer layers of the liquid are extruded from the spinneret at the same time. The inner layer is polyvinyl chloride, and the outer layer is a liquid with lithium ion sieve as the main component. The air bath length is 0.1-1m, and after the coagulation bath, it is solidified into a film through a phase inversion reaction. After the spinning is completed, the silk is heat-treated in pure water at 60-80°C for 2-6h.
[0044] The formed filamentous lithium ion sieve is immersed in pure water for a period of time to displace the organic solvent.
[0045] Preferably, the prepared double-layer filamentary lithium ion screen is cut into short filaments of 1-2 cm by a mechanical cutter, and is acidified with 0.01-0.1M hydrochloric acid, the acidification temperature is 60°C, the acidification end point is that the pH remains unchanged within 20 minutes, and the water inlet form is a bottom-in and top-out cycle experiment. The acidified material is washed with deionized water until the washing liquid is neutral, and a portion of the sample is taken for lithium ion adsorption test.
[0046] One aspect of the present invention also relates to a method for adsorbing lithium ions, using the lithium ion adsorption material to adsorb lithium ions.
[0047] The embodiments of the present invention will be described in detail below with reference to specific examples and comparative examples.
[0048] Example 1
[0049] The method for preparing the lithium ion adsorption material provided in this embodiment comprises the following steps:
[0050] 1. Preparation of spinning solution A: DMAC and polyvinyl chloride (PVC) were mixed and stirred in an oil bath at 60°C for 6 hours. The viscosity of spinning solution A was 6000 mPa·s.
[0051] Preparation of spinning solution B: PVC, lithium ion sieve, dimethylformamide (DMAC), polyvinyl pyrrolidone (PVPK30), and PEG400 were mixed evenly and placed in a 60°C oil bath and stirred for 10 hours;
[0052] The specific amounts of each raw material are shown in Table 1;
[0053] Table 1 Specific amount of each raw material
[0054]
[0055]
[0056] 2. Install the spinning liquid tank and spinneret, and carry out double-layer spinning of the evenly stirred material under the condition of 60℃ coagulation bath temperature. The spinning liquid is pumped by a melt pump. The pumping speed of spinning liquid A is 5Hz / min, and the pumping speed of spinning liquid B is 15Hz / min. The inner and outer layers of the liquid are extruded from the spinneret at the same time. The inner layer is polyvinyl chloride, and the outer layer is the liquid with lithium ion sieve as the main component. The air bath length is 0.2m. After the coagulation bath, the film is solidified by phase inversion reaction. After the spinning is completed, the membrane is heat-treated in 60℃ pure water for 3h. The electron microscope image of the double-layer filamentous lithium ion sieve is as follows Figure 3 As shown;
[0057] 3. Use a mechanical cutter to cut the prepared double-layer filamentary lithium ion sieve into short filaments of 1-2 cm, and use 0.01M hydrochloric acid to acidify the double-layer composite filaments. The acidification temperature is 60°C, and the acidification end point is that the pH remains unchanged within 20 minutes. The water inlet form is a bottom-in and top-out cycle experiment; the acidified material is washed with deionized water until the washing liquid is neutral.
[0058] Example 2
[0059] The method for preparing the lithium ion adsorption material provided in this embodiment comprises the following steps:
[0060] 1. Preparation of spinning solution A: DMAC and PVC were mixed and stirred in an oil bath at 60°C for 8 hours. The viscosity of spinning solution A was 150000 mPa·s.
[0061] Preparation of spinning solution B: PVC, lithium ion sieve, dimethylformamide (DMAC), polyvinyl pyrrolidone (PVPK30), and PEG400 were mixed evenly and placed in a 60°C oil bath and stirred for 10 hours;
[0062] The specific amount of each raw material is shown in Table 2;
[0063] Table 2 Specific amount of each raw material
[0064]
[0065] 2. Install the spinning liquid tank and spinneret, and carry out double-layer spinning of the evenly stirred material under the condition of 60℃ coagulation bath temperature. The spinning liquid is pumped by a melt pump. The pumping speed of spinning liquid A is 10Hz / min, and the pumping speed of spinning liquid B is 50Hz / min. The inner and outer layers of liquid are extruded from the spinneret at the same time. The inner layer is polyvinyl chloride, and the outer layer is liquid with lithium ion sieve as the main component. The air bath length is 0.4m. After the coagulation bath, the film is solidified by phase inversion reaction. After the spinning is completed, the membrane is heat-treated in 60℃ pure water for 3h. The electron microscope picture of the double-layer filamentous lithium ion sieve is as follows Figure 4 As shown;
[0066] 3. Use a mechanical cutter to cut the prepared double-layer filamentary lithium ion sieve into short filaments of 1-2 cm, and use 0.01M hydrochloric acid to acidify the double-layer composite filaments. The acidification temperature is 60°C, and the acidification end point is that the pH remains unchanged within 20 minutes. The water inlet form is a bottom-in and top-out cycle experiment; the acidified material is washed with deionized water until the washing liquid is neutral.
[0067] After testing, the volume adsorption capacity of the sample was 3.6g / L.
[0068] Comparative Example 1
[0069] This comparative example provides a method for preparing a lithium ion adsorption material. The spinning solution A is the same as the spinning solution B of Example 1, and the rest is the same as Example 1.
[0070] Experimental example
[0071] The lithium ion adsorbents prepared in the examples and comparative examples were subjected to adsorption tests. 10 g of lithium ion adsorbent and 1 L of test solution were taken and adsorbed at room temperature for 3 h. The adsorption solution was simulated brine (Li + The theoretical concentration is 300 mg / L, Na + The theoretical concentration is 35 g / L, pH = 9.5), and the adsorption temperature is 25° C. The volume adsorption capacity results are shown in Table 3.
[0072] Table 3
[0073] Group Adsorption capacity g / L Example 1 3.5 Example 2 3.6 Comparative Example 1 2.8
[0074] The lithium ion adsorption materials of the embodiments and comparative examples were tested for long-term operation. The evaluation results are as follows: Figure 5 As shown, it can be seen that the lithium ion adsorption material provided by the present invention can operate stably for a long time.
[0075] In summary, the lithium ion adsorption material provided by the present invention has a large adsorption capacity and strong acid and alkali resistance; the interior is polyvinyl chloride, and the main component of the outer layer is a lithium ion sieve. In the process of engineering application, due to the control of the ion diffusion rate, the internal adsorbent often does not play an effective role. Therefore, the internal acid and alkali resistant pure PVC slurry is used to replace the lithium ion sieve slurry for spinning molding, which can not only improve the utilization rate of the lithium ion sieve and reduce the production cost, but also play a certain supporting role and enhance the pressure resistance of the molded particles.
[0076] The preparation method of the lithium ion adsorbent material provided by the present invention has a simple preparation process and is economical and environmentally friendly. The lithium ion adsorbent produced has strong acid and alkali resistance, large adsorption capacity and low production cost.
[0077] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A lithium ion adsorption material, characterized in that: The lithium ion adsorption material comprises a core and a shell; The core of the lithium ion adsorption material comprises: polyvinyl chloride; the shell of the lithium ion adsorption material comprises: polyvinyl chloride, a lithium ion sieve and a porogen; The thickness ratio of the core and shell of the lithium ion adsorption material is 1:(3-5); The preparation method of the lithium ion adsorption material comprises the following steps: Spinning, acidifying and washing the spinning solution A and the spinning solution B; Wherein, the spinning solution A comprises: polyvinyl chloride; the spinning solution B comprises: polyvinyl chloride, lithium ion sieve and porogen; The porogen includes: polyvinyl pyrrolidone and / or polyethylene glycol; The shell of the lithium ion adsorption material comprises, by weight: 140-170 parts of polyvinyl chloride, 30-60 parts of lithium ion sieve and 25-170 parts of porogen.
2. The lithium ion adsorption material according to claim 1, characterized in that The lithium ion sieve comprises: a titanium-based adsorbent and / or an aluminum-based adsorbent.
3. The method for preparing the lithium ion adsorption material according to claim 1 or 2, characterized in that: The following steps are involved: Spinning, acidifying and washing the spinning solution A and the spinning solution B; Wherein, the spinning solution A comprises: polyvinyl chloride; the spinning solution B comprises: polyvinyl chloride, lithium ion sieve and porogen.
4. The method for preparing a lithium ion adsorption material according to claim 3, characterized in that: The coagulation bath temperature of the spinning is 60-80°C.
5. The method for preparing the lithium ion adsorption material according to claim 3, characterized in that: The air bath length of the spinning is 0.1 to 1 m.
6. The method for preparing the lithium ion adsorption material according to claim 3, characterized in that: The acidification temperature is 55-65°C.
7. The method for preparing the lithium ion adsorption material according to claim 3, characterized in that: The acidified acid solution has a concentration of 0.01 to 0.1M.
8. A method for adsorbing lithium ions, characterized in that: The lithium ion adsorbing material according to claim 1 or 2 is used to adsorb lithium ions.
Citation Information
Patent Citations
Chitosan-lithium ion sieve composite pellet, and preparation method and application thereof
CN111992155A
Preparation method of granular titanium-based lithium ion sieve adsorbent with high adsorption capacity
CN114345291A
Spherical manganese dioxide type lithium ionic sieve
CN101898113A
Functionalized nano-fiber filter material and preparation method and application thereof
CN108579212A
Preparation method of porous spinning composite material and lithium extraction application thereof
CN112619621A
Cited By
Ultrahigh-capacity lithium ion adsorption material as well as preparation method and application thereof
CN117003973A